Aging Alters the Relative Contributions of the Sympathetic and Parasympathetic Nervous System to Blood Pressure Control in Women. Issue 5 (November 2018) - Baker, Sarah E.; Limberg, Jacqueline K.; Dillon, Gabrielle A.; Curry, Timothy B.; Joyner, Michael J.; Nicholson, Wayne T.
Abstract : Autonomic support of blood pressure increases with age in humans. Large differences exist in the dose of trimethaphan (TMP) required for ganglionic blockade in young and older women. We asked whether differences in the dose of TMP required to achieve ganglionic blockade are because of differences in the relative contributions of the sympathetic and parasympathetic nervous system in control of blood pressure with age. Muscle sympathetic nerve activity (microneurography, peroneal nerve), heart rate (HR), and blood pressure were recorded before and during incremental doses of TMP camsylate until ganglionic blockade was achieved (absence of muscle sympathetic nerve activity and <5-bpm increase in HR during a valsalva maneuver; final TMP dose, 1–7 mg/min). HR variability was analyzed from the ECG waveform (WinCPRS). The dose of TMP required to achieve ganglionic blockade is positively related to basal HR variability, where women with high HR variability require a higher dose of TMP to achieve ganglionic blockade. In contrast, baseline muscle sympathetic nerve activity is inversely related with the dose of TMP required to achieve ganglionic blockade, such that women with high basal muscle sympathetic nerve activity required a lower dose of TMP. As such, the change in HR with ganglionic blockade was positively related, and the change in mean arterial pressure was inversely related, with the dose of TMP required to achieve ganglionic blockade. These data suggest loss of parasympathetic tone and increased sympathetic tone with aging contribute to the increase in blood pressure with age in women and dictate the dose of TMP that is necessary to achieve ganglionic blockade.